1996
DOI: 10.1182/blood.v88.5.1747.1747
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of P-glycoprotein in the transmembrane transport of interleukin-2 (IL-2), IL-4, and interferon-gamma in normal human T lymphocytes

Abstract: The physiological role of the multidrug resistance P-glycoprotein (P- gp), which is expressed by normal human T lymphocytes, is still largely unknown. To investigate whether or not P-gp is involved in the transport of cytokines, peripheral blood lymphocytes were stimulated with phytohemagglutinin (PHA) in the absence or presence of P-gp inhibitors, and concentrations of cytokines (interleukin-2 [IL-2], IL- 4, IL-6, interferon-gamma [IFN-gamma]) in the supernatants of these cultures were quantitated by enzyme-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…In addition, TAM did not interfere with T-cell activation as determined by CD25 and CD69 expression in the presence of Con A stimulation in vitro, and the data is similar to that in human T cells. 22 The data here also demonstrated that DN T cells did respond to IL-2-activated activation but poorly to cross-linking anti-CD3 activity or phytohaemagglutinin (PHA) (data not shown). To further understand the effect of TAM on IL-2-activated proliferation of DN T cells, the T cells were pretreated with TAM and then stimulated with IL-2 (1 .…”
Section: Discussionmentioning
confidence: 94%
“…In addition, TAM did not interfere with T-cell activation as determined by CD25 and CD69 expression in the presence of Con A stimulation in vitro, and the data is similar to that in human T cells. 22 The data here also demonstrated that DN T cells did respond to IL-2-activated activation but poorly to cross-linking anti-CD3 activity or phytohaemagglutinin (PHA) (data not shown). To further understand the effect of TAM on IL-2-activated proliferation of DN T cells, the T cells were pretreated with TAM and then stimulated with IL-2 (1 .…”
Section: Discussionmentioning
confidence: 94%
“…Raghu et al (1996) showed that treatment of PHA-activated peripheral blood lymphocytes with P-gp specific monoclonal antibodies resulted in a significant reduction of IL-2 levels in cultures. Drach et al (1996) studied the involvement of P-gp in the transmembrane transport of IL-2, IL-4, IL-6 and IFN-in PHA-stimulated T lymphocytes from healthy subjects. It was revealed that the release of IL-2, IL-4 and IFN-was significantly inhibited by P-gp inhibitors (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Due to postulated P-gp involvement in the transmembrane transport of endogenous proteins, it is also suggested that it has a potential role in the transport of cytokines (Drach et al 1996;Raghu et al 1996). Nevertheless the role of P-gp in the release of cytokines from cells treated with immunosuppressive drugs has to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…More recent evidence suggests ABCB1 may confer resistance to apoptosis by interfering with caspase-8 activation (Ruefli et al, 2002). A role in the secretion of cytokines (Vasquez et al, 2005) has also been suggested which may account for its expression on these cells (Drach et al, 1996).…”
Section: Introductionmentioning
confidence: 99%